Detection of Circulating Tumor Cell Molecular Subtype in Pulmonary Vein Predicting Prognosis of Stage I–III Non-small Cell Lung Cancer Patients - Dong, Jingsi; Zhu, Daxing; Tang, Xiaojun; Qiu, Xiaoming; Lu, Dan; Li, Bingjie; Lin, Dan; Zhou, Qinghua (Frontiers in Oncology, 2019)
Background: There was rare studies on prognosis of pulmonary venous CTC and early or advanced NSCLC patients. We want to investigate whether CTCs and the subtype of it can predict the prognosis of NSCLC patients. Patients and Methods: One hundred and fourteen patients with stage I-III NSCLC were included CanPatrol™ CTC analysis. PD-L1 expression level were detected in CTC of pulmonary vein. PD-L1, number of CTC in pulmonary, CTC's subtype, clinical characteristics, prognosis of patients were analyzed. Results: 110/114 (96.5%) patients could be found CTCs in pulmonary vein, 58/114 (50.9%) patients had CTC≥15/ml in pulmonary vein, 53/110 patients (48.2%) were defined as having MCTC subtype and 56/110 patient were found have PD-L1 (+) CTC in pulmonary vein. Multivariate analyses showed that PVCTC, MCTC, and stage were independent factors of DFS (P < 0.05). No OS difference was found between number of CTC (P = 0.33) and other CTC factors (P > 0.05), only stage was independent factor of OS (P = 0.019). There were decreases of CTC number and MCTC number in EGFR mutant subgroup (P = 0.0009 and P = 0.007). There were increases of CTC (P = 0.0217), MCTC (P = 0.0041), and PD-L1 (+) CTC (P = 0.0002) number in KRAS mutant subgroup. There was increase of MCTC (P =0.0323) number in BRAF mutant. There were fewer CTCs in pulmonary vein for patients with EGFR mutant than in patients with full wild-type gene (P = 0.0346). There were more PD-L1 positive CTCs in pulmonary vein for patients with ALK rearrangement, KRAS mutant, BRAF mutant, or ROS1 mutant than in patients with full wild-type gene (P = 0.0610, P = 0.0003, P = 0.032, and P = 0.0237). There were more mesenchymal CTCs in pulmonary vein for patients with KRAS mutant and BRAF mutant than in patients with full wild-type gene (P = 0.073 and P = 0.0381). There were fewer mesenchymal CTCs in pulmonary vein for patients with EGFR mutant than in patients with full wild-type gene (P = 0.0898). Conclusions: The patients with high number of CTCs, MCTCs, or PD-L1 (+) CTCs in pulmonary vein experienced poor prognosis of DFS. There are obvious correlations between the CTC subtype of NSCLC and the gene subgroups of tumor tissue.